Effects of the antidepressant paroxetine on migratory behaviour of meiobenthic nematodes: Computational and open experimental microcosm approach. (April 2022) - Ishak, Sahar; Allouche, Mohamed; Harrath, Abdel Halim; Alwasel, Saleh; Beyrem, Hamouda; Pacioglu, Octavian; Badraoui, Riadh; Boufahja, Fehmi
Abstract: An open experimental setup was established in order to explore the toxic effects of the antidepressant paroxetine on meiobenthic nematodes. Three types of microcosms made from polyvinyl chloride tubes, each comprising two sediments compartments (upper and lower), were used in a laboratory experiment for 15 days. The experimental setup targeted the migratory behaviour of the nematofauna from the above compartments, which were exposed to paroxetine (0.4 and 40 μg.l −1 ), towards below compartments. The univariate indices significantly decrease in the contaminated compartments compared to controls. Multivariate analyses revealed also significant taxonomic dissimilarities between contaminated and uncontaminated compartments. Furthermore, SIMPER functional outcomes highlighted a significant decrease in 2A feeding groups, 'co' tail shape, 1–2 mm interval length, 'cr' amphid shape, and c-p2 life history in contaminated compartments. Computational approach showed that paroxetine bound GLD-3 and SDP with high affinities, which together with molecular interactions and toxicokinetics satisfactorily explain the experimental results. Highlights: Nematode abundance and diversity decreased under paroxetine contamination. Paroxetine disadvantaged the 2A nematodes with conical tails and circular amphids. Paroxetine bound GLD-3 and SDP with high affinities.